Synthetic environment for forward scattering radar software development / Siti Mas Hidayu Ab Gapor - Ab Gapor, Siti Mas Hidayu (2015)
The aim of this project is developed a software simulation package in MATLAB that provides a convenient tool to estimate the performance and able to predict the signal strength under variety of environmental conditions and kind of targets. This project •r expected the develop program could provide information as GUI displayed on the computer screen. The software model is suitable for instructional purposes due to its user-friendly graphical user interface. It provide the user a platform can interact with, for the tasks of gathering and producing information. In this case, the user can selected the parameter as input such as operating frequency. The program will be gathering all the input and calculate and will produce the graphical result for the user.